Intérprete educacional e o aprender de alunos surdos: análise do contexto remoto no ensino superior - Iriarte, Anne Caroline Santana (Universidade Federal de São Carlos, 2023)
Translation and interpretation in Libras in the educational context has specific complexities that result from the model of inclusive education, which has Portuguese as the language of instruction, thus implying the presence of the interpreter to mediate the knowledge, information, and interactions that take place in the classroom. Besides, the widely dispersed discourses in legal provisions and guidelines do not always coincide with the real practices of educational interpretation, insofar as interpreters, by meeting the other-student, place themselves in a position of active mastership, acting on the frontier between interpreting and teaching, in partnership with regent teachers. With the context of the Covid-19 pandemic, the work of educational interpreters has undergone changes beyond the interpretive act, as the historical moment required other kinds of knowledge, other practices in the face of the new class format: remote teaching. Therefore, this research aims to know inclusive practices in higher education, in a remote context, and understand how they set fundamental pedagogical actions for deaf students to learn through interpretation in Libras. For that, data were collected through interviews with educational interpreters and with a deaf student, in addition to observation with field recording in the virtual classroom of a university in the countryside of the state of São Paulo. The participants' discourses were analyzed based on theoretical studies of the philosophy of difference, through the Deleuzian lens in his concept of learning, in dialogue with the works O mestre inventor and O mestre ignorante, and with authors of Deaf Studies in Education, to discuss the pedagogic function exercised by the interpreter in the remote educational context, under the methodological perspective of a discourse analysis in Michel Foucault. As a result, I point out that, in remote teaching, the active mastership position of the interpreter was even more evident with the creative use of the functionalities of the virtual platforms, such as the written record of important data for the student's learning and the elaboration of interpreted and/or translated recorded materials, with multiple resources. On the other hand, remote teaching, to a certain extent, also distanced relationships in the classroom, limiting the creation of bonds between the deaf student and her hearing teachers and colleagues, which takes place through visuality. For Libras interpreters, the format expanded the possibilities of teamwork and their performance, but the work demands also increased, causing overload with physical and mental symptoms. With this, I hope that the research will contribute to the debate about the training of interpreters for remote work, the preparation of institutions, and the expansion of the offer of materials in Libras for deaf students in the in- person format as well.
Educational interpreter and the learning of deaf student: analysis of the remote context in higher education
Keywords: Intérprete educacional; Aprender; Ensino remoto; Ensino superior; Educational Interpreter; Learning; Remote teaching; Higher education; CIENCIAS HUMANAS::EDUCACAO